International organizations in world politics - Gutner, Tamar L. (Los Angeles : SAGE/ CQ Press, 2017)
"International organizations (IOs) are essential yet controversial actors in world politics today. This timely and engaging new title offers a comprehensive overview of major IOs and their role in global governance. [This book] presents a variety of theoretical approaches to analyzing the roles and impact of IOs. It then offers comprehensive, historically-grounded overviews of the most influential IOs--the United Nations, World Bank, International Monetary Fund, and World Trade Organization. A detailed case study on each illuminates the constraints and challenges it faces in areas such as conflict resolution, development, the environment, trade, and financial crisis. This important new text also examines regional organizations, with an emphasis on the European Union and the euro crisis and the African Union's peace operations."--
Introduction -- Intellectual context : the evolution of IO theory -- United Nations -- United Nations case study : Rwanda/genocide -- The World Bank -- World Bank case study : environmental behavior and performance -- The International Monetary Fund -- International Monetary Fund case study : the IMF and the global financial crisis -- The World Trade Organization -- World Trade Organization case study : intellectual property, trade, and access to medicine -- Regional organizations/European Union -- Regional organizations case study : African Union peace operations.
Includes bibliographical references and index.
Keywords: United Nations; World Bank; International Monetary Fund; World Trade Organization; International Monetary Fund; United Nations; World Bank; World Trade Organization; International agencies; International agencies; Internationale Organisation; Internationale Politik